2020
DOI: 10.1111/jcmm.15511
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of proteins and antibody fragments from transiently transfected endothelial progenitor cells

Abstract: In neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, multiple sclerosis and amyotrophic lateral sclerosis, neuroinflammation can lead to blood‐brain barrier (BBB) breakdown. After intravenous or intra‐arterial injection into mice, endothelial progenitor cells (EPCs) home to the damaged BBB to promote neurovascular repair. Autologous EPCs transfected to express specific therapeutic proteins offer an innovative therapeutic option. Here, we demonstrate that EPC transfection by electropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Therefore, the use of transfected EPCs has been proposed as a possible treatment pathway in AD by taking advantage of their ability to home to the damaged BBB. Recently, transfected EPCs that release antibodies against Aβ and reduce its aggregation have been generated ( Heller et al, 2020 ). However, this novel therapeutic approach has not yet been tested in vivo .…”
Section: Endothelial Progenitor Cells and Their Potential Role In Alz...mentioning
confidence: 99%
“…Therefore, the use of transfected EPCs has been proposed as a possible treatment pathway in AD by taking advantage of their ability to home to the damaged BBB. Recently, transfected EPCs that release antibodies against Aβ and reduce its aggregation have been generated ( Heller et al, 2020 ). However, this novel therapeutic approach has not yet been tested in vivo .…”
Section: Endothelial Progenitor Cells and Their Potential Role In Alz...mentioning
confidence: 99%
“…Transient transfection with anti-β-amyloid Fab encoding vector using electroporation resulted in the production and secretion of Fabs, solubilizing the β-amyloid aggregates as described by Heller, Thinard et al [21].…”
Section: Resultsmentioning
confidence: 99%
“…2). The protein sequence of the active Fab fragments allowed us to build expression vectors containing the respective Fab encoding sequences as well as the insulin gene sequence to facilitate the export of the expressed protein [21].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of lncRNAs is associated with OS in cancer patients. 46 , 47 , 48 , 49 Therefore, we analyzed 19 DE lncRNAs of ceRNA in this study and found differential expression in the Myc high tumor group (n = 185) and Myc low tumor group (n = 186) using the heatmap ( Figure 6 A). Among the 19 DE lncRNAs, we screened potential prognosis-associated lncRNAs by univariate and multivariate Cox regression analyses.…”
Section: Resultsmentioning
confidence: 99%